2008
DOI: 10.4012/dmj.27.633
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Stress Analysis of Titanium Implants by Finite Element Method

Abstract: With use of dental implants on the rise, there is also a tandem increase in the number of implant fracture reports. To the end of investigating the stress occurring in implants, elasticity and plasticity analyses were performed using the finite element method. The following results were obtained:(1) With one-piece type of implants of 3.3 mm diameter, elasticity analysis showed that after applying 500 N in a 45-degree direction, stress exceeding 500 MPa -which is the proof stress of grade 4 pure titanium -occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…In this study, up to 800 N of vertical loading was applied as an arbitrary maximum occlusal force for molars . Although previous in vitro studies have reported that varying implant/abutment connection systems exhibit sufficient joint strength to withstand heavy loading, the current study revealed that the overload condition resulted in some amount of axial displacement and preload loss, which might detrimental to sustain joint stability. Excessive occlusal load challenges the implant and its prosthetic components, which might lead to biomechanical complications.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In this study, up to 800 N of vertical loading was applied as an arbitrary maximum occlusal force for molars . Although previous in vitro studies have reported that varying implant/abutment connection systems exhibit sufficient joint strength to withstand heavy loading, the current study revealed that the overload condition resulted in some amount of axial displacement and preload loss, which might detrimental to sustain joint stability. Excessive occlusal load challenges the implant and its prosthetic components, which might lead to biomechanical complications.…”
Section: Discussionmentioning
confidence: 79%
“…No fracture failure or plastic deformation of the implant/abutment complex was detected after 500 N of cyclic loading; 500 N was adopted as an arbitrary overload condition imitating the functional environment of the second molar area . Several in vitro studies of implant cyclic loading adopted ISO 14801 test setup with worst‐case scenario and applied a relatively low loading condition, ranging from 50 to 150 N. Some in vitro and finite element model studies reported 500 N as the maximum failure strength of implants made of commercially pure titanium (cp Ti‐grade 4) that plastic deformation could occur under oblique loading . Unlike those studies, our study aimed to evaluate the overloading environment with maximized axial displacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The same can be said for the implant, which showed much higher stress concentration when submitted to oblique load. 32 Stress exceeding 1 GPa, which is larger than the proof stress of 900 MPa of Ti-6Al-4 V alloy, 29 was concentrated in the implant neck. The numerical results, however, might be influenced by the boundary conditions, once the surfaces were considered perfectly bonded and, thus, the abutment was not able to rotate and move away from the implant platform.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with other studies, which stated that oblique load is associated with higher stresses. 16,29 It is important to emphasize that oblique load application has been related to more realistic occlusal loading. 11 The abutment screw fracture is a frequent problem in the clinical field.…”
Section: Discussionmentioning
confidence: 99%